Adult Neural Precursor Cells from the Subventricular Zone Contribute Significantly to Oligodendrocyte Regeneration and Remyelination - Xing, Yao Lulu; Röth, Philipp T.; Stratton, Jo Anne S.; Chuang, Bernard H.A.; Danne, Jill; Ellis, Sarah L.; Ng, Sze Woei; Kilpatrick, Trevor J.; Merson, Tobias D. (The Journal of neuroscience, 2014)
Parenchymal oligodendrocyte progenitor cells (pOPCs) are considered the principal cell type responsible for oligodendrogenesis and remyelinaton in demyelinating diseases. Recent studies have demonstrated that neural precursor cells (NPCs) from the adult subventricular zone (SVZ) can also generate new oligodendrocytes after demyelination. However, the relative contribution of NPCs versus pOPCs to remyelination is unknown. We used in vivo genetic fate mapping to assess the behavior of each progenitor type within the corpus callosi (CCs) of mice subjected to cuprizone-induced demyelination. Nestin-CreER T2 and Pdgfra-CreER T2 transgenic mice were crossed with fluorescent Cre reporter strains to map the fate of NPCs and pOPCs respectively. In cuprizone-challenged mice, substantial numbers of NPCs migrated into the demyelinated CC and contributed to oligodendrogenesis. This capacity was most prominent in rostral regions adjacent to the SVZ where NPC-derived oligodendrocytes significantly outnumbered those generated from pOPCs. Sixty-two percent of all nodes of Ranvier in this region were flanked by at least one paranode generated from an NPC-derived oligodendrocyte. Remarkably, g-ratios (ratio of the axon diameter to the diameter of the axon plus myelin sheath) of myelinated axons in regions subject to significant NPC-derived remyelination were equivalent to those of unchallenged controls, and immunoelectron microscopy revealed that NPC-derived myelin was significantly thicker than that generated by pOPCs, regardless of axonal caliber. We also demonstrate that a reduced efficiency of remyelination in the caudal CC was associated with long-term impairment in the maturation of oligodendrogenic NPCs but only transient delay in pOPC differentiation. Collectively, our data define a major distinct role for NPCs in remyelination, identifying them as a key target for enhancing myelin repair in demyelinating diseases.